Pre-service teachers’ awareness of students’ learning styles and adaptation of speaking instruction in EFL classrooms - Arlinda Dwita Ramadianti; Putu Dian Danayanti Degeng (Educenter : Jurnal Ilmiah Pendidikan, 2026)
This study investigated pre-service teachers’ awareness of students’ learning styles and their strategy adaptation in English as a Foreign Language (EFL) speaking classrooms. The study employed a descriptive quantitative design using a questionnaire consisting of 12 items covering four aspects: awareness of different learning styles, awareness of learning styles in speaking contexts, speaking instructional strategy adaptation, and multimodal and task-based speaking support. The participants were 66 seventh-semester students of the English Language Education Program at one of prominent universities in Malang who had completed their teaching practicum during the 2025/2026 academic year. The participants were selected using purposive sampling because they had prior teaching experience through teaching practicum in EFL classrooms. Data analysis included coding questionnaire responses, conducting reliability analysis using Cronbach’s Alpha, calculating mean and standard deviation values, and interpreting the results based on predetermined category intervals. The findings revealed that pre-service teachers demonstrated a very high level of awareness of students’ varied learning styles and recognized the importance of adapting speaking instruction to accommodate these differences. The results also indicated that participants perceived varied speaking strategies and multimodal resources as important in supporting diverse learners. The findings highlight the importance of integrating differentiated instruction and learning style awareness in teacher education programs.